Orbital and physical parameters of eclipsing binaries from the ASAS catalogue – XII. A sample of systems with K2 photometry. Issue 4 (14th October 2021) - Hełminiak, K G; Moharana, A; Pawar, T; Ukita, N; Sybilski, P; Espinoza, N; Kambe, E; Ratajczak, M; Jordán, A; Maehara, H; Brahm, R; Kozłowski, S K; et al.
ABSTRACT: We present results of the analysis of light and radial velocity (RV) curves of eight detached eclipsing binaries observed by the All-Sky Automated Survey, which we have followed up with high-resolution spectroscopy, and were later observed by the Kepler satellite as part of the K2 mission. The RV measurements came from spectra obtained with OAO-188/HIDES, MPG-2.2 m/FEROS, SMARTS 1.5 m/CHIRON, Euler/CORALIE, ESO-3.6 m/HARPS, and OHP-1.93/ELODIE instruments. The K2 time-series photometry was analysed with the jktebop code, with out-of-eclipse modulations of different origin taken into account. Individual component spectra were retrieved with the fd3 code, and analysed with the code ispec in order to determine effective temperatures and metallicities. Absolute values of masses, radii, and other stellar parameters are calculated, as well as ages, found through isochrone fitting. For five systems, such analysis has been done for the first time. The presented sample consists of a variety of stars, from low-mass dwarfs, through G- and F-type main sequence objects, to evolved active sub-giants, one of which is found to be crossing the Hertzsprung gap. One target may contain a γ Dor-type pulsator, two more are parts of higher-order multiples, and spectra of their tertiaries were also retrieved and used to constrain the properties of these systems.